PENGARUH TRANSFORMASIONAL LEADERSHIP TERHADAP ORGANIZATIONAL PERFORMANCE MELALUI ORGANIZATIONAL LEARNING DAN INOVAS - Ray mond; Mohamad Gita Indrawan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The aim of the study was to find out to find out the influence of transformational leadership both theoretically and empirically with its relation to organizational performance through organization learning and to find out the influence of transformational leadership both theoretically and empirically with its relation to Organizational performance through innovation. The validity of the tested statement uses factor analysis. Item statements will be estimated if the factor loading value is less than 0.5 and will be maintained if more than or equal to the cut-off value, Test reliability is done with Cronbach's Alpha. Hypothesis testing will be tested with Partial Least Square (PLS) which is part of Structural Equation Modeling (SEM). The results of this study found that Transformational Leadership had an effect on Organizational Learning at PT PLN Batam. Transformational Leadership influences Innovation at PT PLN Batam. Organizational Learning influences innovation at PT PLN Batam. Organizational learning has no effect on organizational performance at PT PLN